2021
DOI: 10.1111/trf.16671
|View full text |Cite
|
Sign up to set email alerts
|

Fear is associated with attrition of first‐time whole blood donors: A longitudinal examination of donor confidence and attitude as potential mediators

Abstract: Background: Elevated fear and anxiety regarding donation-related stimuli (e.g., needles, pain, blood, fainting) has been associated with reduced blood donor recruitment and retention. The present longitudinal study tests the notion that this inverse relationship may be accounted for by lower donation confidence and more negative donation attitudes among fearful first-time donors.Study Design and Methods: In a sample of 1479 first-time whole blood donors [67.9% female; mean age = 19.3 (standard deviation (SD) =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The aging donor population has been, in part, attributed to the declining engagement of younger donors who have been characterized as disinterested in volunteerism relative to older generations. 33,34 It is unknown whether this characterization is particularly true of modern young people, or whether this characterization of younger people as "selfish" represents typical generational rivalry. 35,36 While it may be tempting to categorize donors based on their traditional generational buckets (i.e., Baby Boomers, Millennials, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The aging donor population has been, in part, attributed to the declining engagement of younger donors who have been characterized as disinterested in volunteerism relative to older generations. 33,34 It is unknown whether this characterization is particularly true of modern young people, or whether this characterization of younger people as "selfish" represents typical generational rivalry. 35,36 While it may be tempting to categorize donors based on their traditional generational buckets (i.e., Baby Boomers, Millennials, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Fear of seeing own blood, fear of the procedure itself and negative experiences from previous, first-time blood donation or lack of appropriate "incentives", eg, financial, may be an additional barrier for young people. [17][18][19][20][21][22][23][24][25] Interestingly, women, who are more altruistic than men and more motivated to donate blood, 19 accounted for only 1/4-1/3 of all donors in our analysis (Table 3). On the other hand, a similar proportion of female blood donors was also observed in other countries.…”
Section: Dovepressmentioning
confidence: 93%
“…While the emphasis has been on the donor's health and the likelihood that his or her donation has risks for infectious contamination, a donor interview could be an opportunity to address other issues. In a study by France and co‐workers, donation anxiety was revealed as a significant inhibitor of repeat donation by first‐time donors 23 . The investigators suggested that novice donors be asked if they were anxious about donating and, if they answered in the affirmative, they should be given information that could point to coping mechanisms for them to employ 24 .…”
Section: Figurementioning
confidence: 99%
“…In a study by France and co-workers, donation anxiety was revealed as a significant inhibitor of repeat donation by first-time donors. 23 The investigators suggested that novice donors be asked if they were anxious about donating and, if they answered in the affirmative, they should be given information that could point to coping mechanisms for them to employ. 24 In another study that also looked at a very different role for a donor questionnaire, Livitz and co-workers explored "motivational interviewing" as a strategy to increase the likelihood that individuals would donate.…”
mentioning
confidence: 99%